Construct validity of the Arabic version of the opinion relative to integration of student with disabilities scale - Khalid N. Alasim; Bandar M. Almohayya (PLoS ONE, 2026)
This study investigated the construct validity and psychometric properties of the Arabic version of the Opinion Relative to the Integration of Students with Disabilities (ORI) scale. Data were collected from 400 general and special education teachers as well as university faculty members. Exploratory factor analyses revealed a four-factor structure explaining 51.37% of the variance. Confirmatory factor analysis of the 15-item model demonstrated acceptable fit after item refinement. Subscale Cronbach’s α values ranged from.60 to.78, reflecting acceptable but marginal internal consistency in some subscales, with a total α of.75 (Cronbach’s α = .60–.78; total α = .75). Reliability indicators were further evaluated using Cronbach’s alpha and the convergent validity was assessed using the Average Variance Extracted (AVE), and Pearson correlation. The findings indicate that university faculty members and teachers generally hold positive attitudes toward inclusion and confirm that the Arabic ORI is a reliable and valid tool for assessing such attitudes. These results provide evidence supporting the instrument’s use in research and policy initiatives aimed at promoting inclusive education across Arabic-speaking contexts.